Unique Features Of Painting In The Professional Training Of Fine Art Teachers - Islam Mengnorov Jumanazarovich (Genius Journals, 2022)
The article analyzes the theoretical ideas and considerations, as well as the practical application of graphics, which is a type of art, and the uniqueness of the role of a pen in painting
Keywords: fine arts; type; genre; pencil